Aplikasi Sistem Informasi Buku Induk Siswa pada MA Putri Taruna Al-Quran - Melany Mustika Dewi (Universitas Lancang Kuning, 2022)
Each educational institution records important data for each student for both school and outside school needs. Important student data is recorded in a book called Student's Main Book. Some schools use computers as a substitute for student books, namely using Microsoft Excel. However the use of Ms. Excel sometimes causes problems, such as what happened at MA Putri Taruna Al-Quran, often experiencing failure to input data to the central server in the form of excel or csv to fill in the national exam data, data loss and damage often occurs, then on the computer there are many duplicate files so that difficulty recognizing which file contains the main data. To overcome these problems, a website-based information system was built. This information system will be equipped with features that can present reports according to the desired column and can also be exported to several extensions. Making this system will be done by several methods such as the method of observation, interviews and literature reviews so as to produce an application called Student Master Book.